2021
DOI: 10.1186/s43088-021-00101-2
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activities of phenolic compounds from Moringa oleifera leaves: in vitro and in silico mechanistic study

Abstract: Background Moringa oleifera is a common vegetable in many countries since ancient times, possesses numerous phenolic compounds having a wide array of biological activities. It possesses anticancer activity that can be used to develop new drugs for treatment of various types of cancers. The current study was conducted to evaluate the composition of phenolic compounds and in vitro and in silico anticancer activities of M. oleifera leaves extracts. The leaves of M. oleifera were subjected to extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 53 publications
1
14
0
5
Order By: Relevance
“…It contains a variety of beneficial components, including flavonoids, phenols, and vitamin C (ascorbic acid), a-tocopherol, and b-carotenoids, etc. ( Alhakmani et al, 2013 , Barhoi et al, 2021 , Mumtaz et al, 2021 , Singhal et al, 2012 , Weon et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It contains a variety of beneficial components, including flavonoids, phenols, and vitamin C (ascorbic acid), a-tocopherol, and b-carotenoids, etc. ( Alhakmani et al, 2013 , Barhoi et al, 2021 , Mumtaz et al, 2021 , Singhal et al, 2012 , Weon et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, many compounds in the plain SLY control sample (C) decreased with storage, such as Octadecane, 3-ethyl-5-(2-ethylbutyl), which has antioxidant and anti-inflammatory effect [ 49 ], 1-Nonadecene, which has antifungal and anticancer effects [ 50 ], Phthalic acid derivatives, which have a role in chronic cardiovascular and cerebrovascular diseases treatments and illustrated its ability in antitumor, anti-inflammatory, and antibacterial activities [ 51 ] and Ethanol, 2-(octadecyloxy) (which has antimicrobial effect [ 52 ])The data in our study revealed that the addition of REO showed new compounds, such as Camphene, which inhibits the biosynthesis of cholesterol and has a promising potential as a lipid-lowering agent [ 53 ], 3-Carene which shows a protective effect in postharvest pathogens [ 54 ], Limonene, which has lemongrass herbal aroma, and has a curative effect on heartburn and gastroesophageal reflux [ 55 , 56 ], 1,6-Octadien-3-ol, 3,7-di methyl-, which has anti-inflammatory and anti-cancer properties [ 49 ], Camphor, which has an important role in cough and colds cure [ 57 ], Bornyl acetate, which has pine, woody, and camphoreous flavors [ 58 , 59 ], Caryophyllene, which has antitumor, analgesic, antibacterial, anti-inflammatory, sedative, and fungicide properties [ 60 ], Copaene (causes an increase in antioxidant capacity of human lymphocyte [ 61 ]), Retinol (which is converted in the human body and is important in vision physiology [ 62 ]), and Aromadendrene oxide-(2) (which has anticancer activity [ 63 ]); however, the storage period declines these compounds. Furthermore, our data illustrate other compounds found in both REO and SLY control samples, which decreased with storage, such as Octadecanal 2-bromo- (which has anti-inflammatory and anti-apoptotic effects [ 64 ]), 1-Heptatriacotanol (which has antioxidant, anticancer and anti-inflammatory effects [ 65 ]), Cyclic methyl boronate (which has a preservative activity [ 60 ]), 3-Pyridinecarboxylic acid,2,7,10-tris(acetyloxy)-11a,2,3,4,6,7,10,11,11a-decahydro-1,1,3,6,9-penta methyl-4-oxo-4a,7aepoxy-5H-yclopenta[a]cyclopropa[f]cycloundecen-11-ylester,[1aR-], which has anti-inflammatory effect [ 64 ], Cinnamic acid, 4-hydroxy-3-methoxy- (which has a promising potential as an anticancer treatment) [ 66 ], Ocimene (has a sweet herbal odor [ 67 ]), and 1-Monolinoleoylglycerol trim ethyl silyl ether (which has antimicrobial activity [ 68 ]); in contrast, other compounds increase with storage, such as 9-Octadecenoic acid,(2-phenyl-1,3-dioxola...…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our data illustrate other compounds found in both REO and SLY control samples, which decreased with storage, such as Octadecanal 2-bromo- (which has anti-inflammatory and anti-apoptotic effects [ 64 ]), 1-Heptatriacotanol (which has antioxidant, anticancer and anti-inflammatory effects [ 65 ]), Cyclic methyl boronate (which has a preservative activity [ 60 ]), 3-Pyridinecarboxylic acid,2,7,10-tris(acetyloxy)-11a,2,3,4,6,7,10,11,11a-decahydro-1,1,3,6,9-penta methyl-4-oxo-4a,7aepoxy-5H-yclopenta[a]cyclopropa[f]cycloundecen-11-ylester,[1aR-], which has anti-inflammatory effect [ 64 ], Cinnamic acid, 4-hydroxy-3-methoxy- (which has a promising potential as an anticancer treatment) [ 66 ], Ocimene (has a sweet herbal odor [ 67 ]), and 1-Monolinoleoylglycerol trim ethyl silyl ether (which has antimicrobial activity [ 68 ]); in contrast, other compounds increase with storage, such as 9-Octadecenoic acid,(2-phenyl-1,3-dioxolan-4-yl) methyl ester trans (which has antimicrobial and anti-inflammatory properties [ 69 ]), 9,12,15-Octadecatrienoic acid, 2-phenyl-1,3-dioxan-5-yl ester (which has antimicrobial and anti-inflammatory properties [ 69 ]), Butanoic acid,1a,2,5,5a,6,9,10,10a-octahydro (indeed, acid compounds (including Butanoic acid) increased after either 3 or 7 days of storage [ 70 ]), 7,8-Epoxylanostan-11-ol, 3-acetoxy- (which has antimicrobial and anti-inflammatory effects [ 71 , 72 ]), and 6,9,12,15-docosatetraenoic acid, methyl ester (which has anti-carcinogenic and anti-atherosclerotic effects [ 73 ]). Meanwhile, other compounds were enhanced in SLY samples after REO addition, such as ester compounds (even at low concentrations, it contributed to the flavors of dairy products [ 74 ]), Eucalyptol, which has a eucalyptus, bark lavender, fresh mint -like fragrance, spicy aroma, and taste [ 52 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy is attributable to polyphenols such as flavonoids, tannins, and terpenoids. Although polyphenols have antineoplastic effects, they are characterized by poor plasma membrane permeability and lipid immiscibility due to their hydrophilic nature, which limits their absorption into the target cells and also lowers their bioavailability and therapeutic efficacy [ 10 , 14 , 15 ]. Moringa oleifera polyphenols (Mopp) are also degraded by digestive enzymes and gastric fluids when administered orally [ 15 ].…”
Section: Introductionmentioning
confidence: 99%